Fall Prevention: Solutions for Your Home - Leigh Ann Martin; Emily Minton (EDIS)
Revised! FCS2228, a 2-page fact sheet by Leigh Ann Martin and Emily Minton lists possible hazards in your home for people growing older and modifications that can be made to prevent falls. Includes additional sources of information. Published by the UF Department of Family, Youth and Community Sciences, March 2010.